Health Literacy, Health Numeracy, and Trust in Doctor: Effects on Key Patient Health Outcomes. Issue 1 (17th July 2019) - Netemeyer, Richard G.; Dobolyi, David G.; Abbasi, Ahmed; Clifford, Gari; Taylor, Herman
Abstract : This research examines the roles of health literacy, health numeracy, and trust in doctor on: (1) patient anxiety when consulting a doctor; (2) frequency of physician consultations; and (3) patient subjective well‐being (SWB). Our sample consisted of 4, 040 adults representative of the United States in terms of age, income, and education, but equally split among White/Caucasian (50%) and Black/African American (50%) respondents. We found that functional and communicative health literacy and trust in doctor have linear and curvilinear relationships with anxiety when consulting a doctor. Health numeracy had no effect. Anxiety when consulting a doctor was associated with a lower number of physician consultations and lower SWB. We observed direct linear effects of health literacy, health numeracy, and trust in doctor on frequency of physician consultations and SWB, as well as some curvilinear effects. We found a negative relationship between health numeracy and SWB. We discuss implications of these findings for health and public policy.